2019
DOI: 10.1124/mol.118.114363
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Tryptophan, the Target of Antineoplastic C-Terminal Binding Protein Inhibitors, Mediates Inhibitor Disruption of CtBP Oligomerization and Transcription Coregulatory Activities

Abstract: C-terminal binding proteins (CtBP1/2) are oncogenic transcriptional coregulators and dehydrogenases often overexpressed in multiple solid tumors, including breast, colon, and ovarian cancer, and associated with poor survival. CtBPs act by repressing expression of genes responsible for apoptosis (e.g., PUMA, BIK) and metastasis-associated epithelial-mesenchymal transition (e.g., CDH1), and by activating expression of genes that promote migratory and invasive properties of cancer cells (e.g., TIAM1) and genes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
4
11
1
Order By: Relevance
“…Similarly, the best-fit molecular masses of CtBP2 in the presence of NAD + or CtBP1 with either nucleotide also correspond to tetramer. These results agree with our previous light scattering analysis of CtBP1 and CtBP2 [31] and indicate that the SV feature near 6 S populated in the presence of nucleotide is associated with the tetramer rather than dimer, as has been previously suggested [36]. We then assign the 4.1 S feature to dimer.…”
Section: Assembly State Of Ctbp1 and Ctbp2supporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, the best-fit molecular masses of CtBP2 in the presence of NAD + or CtBP1 with either nucleotide also correspond to tetramer. These results agree with our previous light scattering analysis of CtBP1 and CtBP2 [31] and indicate that the SV feature near 6 S populated in the presence of nucleotide is associated with the tetramer rather than dimer, as has been previously suggested [36]. We then assign the 4.1 S feature to dimer.…”
Section: Assembly State Of Ctbp1 and Ctbp2supporting
confidence: 92%
“…Here, we investigate the NAD(H)-linked assembly of CtBP through analytical ultracentrifugation and isothermal titration calorimetry (ITC). Despite earlier interpretations of sedimentation velocity (SV) data as deriving from a monomer to dimer assembly [36], we definitively show using both SV and sedimentation equilibrium (SE) that the NAD(H) bound forms of both CtBP1 and CtBP2 are predominantly tetrameric in solution at micromolar concentrations. This tetrameric assembly is fairly stableour SV experiments show that the tetramer to dimer dissociation constants for CtBP1 and CtBP2 in the presence of saturating NADH or NAD + are around 100 nM.…”
contrasting
confidence: 97%
See 1 more Smart Citation
“…Pharmacologic reduction of NADH depolymerizes CtBP, resulting in induction of certain normally repressed target genes 54,55 . Since CtBP dimers can be disrupted not only by reduction in NADH level, but also by small molecule CtBP dehydrogenase inhibitors 56 , a promising approach for treatment of HGSOC and other CtBP dependent cancers that is currently under investigation may be combining small molecule CtBP inhibition with strategies that reduce cellular NADH level 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may function as a transcriptional co-repressor, negatively regulating certain tumor suppressors, thereby promoting the occurrence and development of tumors (17,18). Recent studies have revealed that the CtBP family plays a crucial role in the occurrence and development of breast, colon, ovarian and prostate cancer (19)(20)(21).…”
Section: Ctbp2 Interacts With Tgif To Promote the Progression Of Esophageal Squamous Cell Cancer Through The Wnt/β-catenin Pathwaymentioning
confidence: 99%